2004
DOI: 10.1093/tropej/50.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Screening Programme for Phenylketonuria in the Gaza Strip: Evaluation and Recommendations

Abstract: Phenylketonruia (PKU) is an inherited metabolic disorder that results in progressive mental retardation. PKU is a paradigm of a disease that can be identified by proper screening of newborns and medical follow-up in order to prevent serious complications. The present study was designed to evaluate the Palestinian national screening programme for PKU in the Gaza Strip. Data about the screening of PKU in the Gaza Strip were obtained from the records of the healthcare centers of the Palestinian Ministry of Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Other studies conducted in Iraq [37] indicated that all 7 cases detected with PKU had consanguineous parents. These findings were consistent with previous studies where 57% of PKU patients in Egypt [26], 60% of PKU cases in Gaza Strip [19], 86.6% of PKU patients in Iran [22], and 34 patients out of 43 PKU cases from Iran [31] had consanguineous parents. Similarly, a recent study conducted in 2017 in Mazandaran Province in Iran indicated that parental family relationships among confirmed PKU cases were 53.6% [24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other studies conducted in Iraq [37] indicated that all 7 cases detected with PKU had consanguineous parents. These findings were consistent with previous studies where 57% of PKU patients in Egypt [26], 60% of PKU cases in Gaza Strip [19], 86.6% of PKU patients in Iran [22], and 34 patients out of 43 PKU cases from Iran [31] had consanguineous parents. Similarly, a recent study conducted in 2017 in Mazandaran Province in Iran indicated that parental family relationships among confirmed PKU cases were 53.6% [24].…”
Section: Discussionsupporting
confidence: 93%
“…In some of the prevalence/incidence studies, prevalence was self-calculated in 9 articles and corrected in 11 articles. Prevalence/incidence studies were further categorized to the type of study whether it was a national NBS program ( n = 5 articles) [6, 15–18], regional/governorate NBS program ( n = 6 articles) [1924], selective screening for newborns ( n = 6 articles) [2530], selective screening of sick/symptomatic newborns and/or infants, children, and adults ( n = 9 articles) [3139], selective screening for both newborns and sick/symptomatic newborns and/or infants, children, and adults ( n = 4 articles) [4043], or selective screening for sick/symptomatic children and adults from institutions for mentally challenged ( n = 3 articles) [4446]. In addition, a study conducted in Turkey addressed PKU prevalence among newborns, sick/symptomatic subjects, and mentally challenged individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted in the Gaza Strip, in the Palestinian Territories, showed that 61% of the collections occurred between the 11th and 17th day of life 18 . In Brazil, in Porto Alegre city, the average was 11 days; 19 in Sergipe State 17 days, with 50% of samples being collected in children older than 28 days; 20 in Campina Grande city, the average was 29.8 days, 21 and in Marília, São Paulo State, the average was 27 days 22 …”
Section: Discussionmentioning
confidence: 99%
“…40 As far as legitimacy is concerned, one should read carefully the reports produced by scholars associated with the two parties. Thus for instance the report produced by Ali Abu-Shahla, Anat Cygielman, and Ata Qaymari seems to be part of an official Fatah discourse that attempts to delegitimise Hamas rule in Gaza.…”
Section: Rival: Internal Palestinian Perspectivesmentioning
confidence: 99%